2014
DOI: 10.1007/s00423-014-1191-9
|View full text |Cite
|
Sign up to set email alerts
|

Current strategies for immunosuppression following liver transplantation

Abstract: Along with steroid reduction or elimination, current strategies for IS after LTx continue to explore novel combinations of agents, with an aim toward striking a balance between diminution of rejection and the need for avoiding adverse effects of the IS drugs. Long-term maintenance strategies are also discussed in this review, as is development of tolerance and antibody-mediated rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
0
14
1
Order By: Relevance
“…In a randomized multicenter study, Klintmalm et al [50] concluded that adds to the cost of perioperative care. Antibodies used for induction of immunosuppression in LT are classified into two groups; T-cell depleting and nondepleting [interleukin 2 receptor antagonists (IL 2Ra)] [26] .…”
Section: Non-depleting Antibodiesmentioning
confidence: 99%
“…In a randomized multicenter study, Klintmalm et al [50] concluded that adds to the cost of perioperative care. Antibodies used for induction of immunosuppression in LT are classified into two groups; T-cell depleting and nondepleting [interleukin 2 receptor antagonists (IL 2Ra)] [26] .…”
Section: Non-depleting Antibodiesmentioning
confidence: 99%
“…Calcineurin inhibitors (CNIs) have been a cornerstone of immunosuppressive therapy after solid organ transplantation, significantly reducing the risk of graft rejection. CNIs, however, are associated with severe adverse effects, such as renal dysfunction, resulting in the reduction of their short-and long-term use [3,4]. Furthermore, mortality rates are higher in LT recipients with vs. without post-transplant renal dysfunction [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Crucially, antiviral treatments are reducing viral liver disease, permitting non-alcoholic fatty and alcoholic liver disease, including alcoholic hepatitis in recent years, to emerge as the leading indications for listing. 3,4 Crucially, antiviral treatments are reducing viral liver disease, permitting non-alcoholic fatty and alcoholic liver disease, including alcoholic hepatitis in recent years, to emerge as the leading indications for listing.…”
mentioning
confidence: 99%